2019
DOI: 10.1002/mus.26618
|View full text |Cite
|
Sign up to set email alerts
|

Is carpal tunnel syndrome in the elderly a separate entity? Evidence from median nerve ultrasound

Abstract: http://onlinelibrary.wiley.com/doi/10.1002/mus.26496/full.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…In this study, nerve stiffness was increased in older CTS patients. Some authors have speculated recently that CTS in the elderly may be a separate entity 23,24 . Median nerve CSA may be a less sensitive indicator for CTS in older patients as older CTS patients tend to have smaller CSA.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, nerve stiffness was increased in older CTS patients. Some authors have speculated recently that CTS in the elderly may be a separate entity 23,24 . Median nerve CSA may be a less sensitive indicator for CTS in older patients as older CTS patients tend to have smaller CSA.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor influencing the results might be the patients' age. In very recent studies, it has been demonstrated that the diagnostic accuracy of HRUS in grading CTS is reduced [17][18][19] in older patients. Unfortunately, age was not controlled in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, patient age has been shown to have an effect on the diagnostic accuracy of HRUS in determining the diagnosis and categorizing of the severity of CTS ( Moschovos et al, 2019 , Gregoris and Bland, 2019 ). In this present study, a slight negative correlation between patient age and wCSA was found, which is in line with the previous literature ( Moschovos et al, 2019 , Gregoris and Bland, 2019 ). However, fCSA did not show a similar correlation, indicating that age does not affect fCSA, at least in patients with moderate to extremely severe CTS.…”
Section: Discussionmentioning
confidence: 99%